A Second CRM1-Dependent Nuclear Export Signal in the Influenza A Virus NS2 Protein Contributes to the Nuclear Export of Viral Ribonucleoproteins - Huang, Shengping (American Society for Microbiology, 2013)
Influenza A virus NS2 protein, also called nuclear export protein (NEP), is crucial for the nuclear export of viral ribonucleoproteins. However, the molecular mechanisms of NEP mediation in this process remain incompletely understood. A leucine-rich nuclear export signal (NES2) in NEP, located at the predicted N2 helix of the N-terminal domain, was identified in the present study. NES2 was demonstrated to be a transferable NES, with its nuclear export activity depending on the nuclear export receptor chromosome region maintenance 1 (CRM1)-mediated pathway. The interaction between NEP and CRM1 is coordinately regulated by both the previously reported NES (NES1) and now the new NES2. Deletion of the NES1 enhances the interaction between NEP and CRM1, and deletion of the NES1 and NES2 motifs completely abolishes this interaction. Moreover, NES2 interacts with CRM1 in the mammalian two-hybrid system. Mutant viruses containing NES2 alterations generated by reversed genetics exhibit reduced viral growth and delay in the nuclear export of viral ribonucleoproteins (vRNPs). The NES2 motif is highly conserved in the influenza A and B viruses. The results demonstrate that leucine-rich NES2 is involved in the nuclear export of vRNPs and contributes to the understanding of nucleocytoplasmic transport of influenza virus vRNPs.